MONPERA DALAM MEMORI KOLEKTIF MASYARAKAT KOTA PALEMBANG TAHUN 1945-1947 - Sartikah, Sartikah (Program Studi Sejarah Peradaban Islam, 2024)
The monument to the people's struggle in the city of Palembang or what is often known and referred to as MONPERA is a silent witness to the people's struggle to seize and defend Indonesia's independence from the Dutch colonialists. MONPERA has a collective memory that is very important for the people of Palembang city. And the aim of this research is to find out how the monument of the people's struggle is in the collective memory of the people of Palembang city in 1945-1947. The method used in this research is the historical method, the first step is (hiuristic) data collection, namely in the form of primary data and secondary data. taken from journals and books. The next step (verification) of data is sorting valid data, and the next step is (interpretation) history or historical interpretation of the data that has been collected, and the final step is (historiography) or writing history. And the results of this research show that MONPERA in the collective memory of the people of Palembang city has a very important memory and needs to be understood by the people, not only as a form of monument but at least it must be a memory to reveal the memory of the past as a form of struggle of the people of Palembang city against the Dutch colonialists. Or against colonialism in Palembang.